Microfluidic platform for controlling the differentiation of embryoid bodies - Fung, Wai-To (2012)
Embryonic stem (ES) cells are pluripotent cells, which can differentiate into any cell type. This cell type has often been implicated as an eminent source of renewable cells for tissue regeneration and cellular replacement therapies. Studies on manipulation of the various differentiation pathways have been at the forefront of research. There are many ways in which ES cells can be differentiated. One of the most common techniques is to initiate the development of embryoid bodies (EBs) by in vitro aggregation of ES cells. Thereafter, EBs can be induced to undergo differentiation into various cell lineages. In this article, we present a microfluidic platform using biocompatible materials, which is suitable for culturing EBs. The platform is based on a Y-channel device with two inlets for two different culturing media. An EB is located across both streams. Using the laminar characteristics at low Reynolds number and high Peclet numbers, we have induced cell differentiation on half of the EB while maintaining the other half in un-induced stages. The results prove the potential of using microfluidic technology for manipulation of EBs and ES cells in tissue engineering.